Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1161/01.atv.0000077206.35631.b2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of von Willebrand Factor to Thrombus Formation on Neointima of Rabbit Stenotic Iliac Artery Under High Blood-Flow Velocity

Abstract: Objective-It has become clear that von Willebrand factor (vWF) plays important roles in platelet adhesion and aggregation under high blood-flow velocity conditions observed in stenotic atherosclerotic arteries. However, its roles in thrombus formation in vivo on diseased arteries have not been fully understood. We examined the contribution of vWF to thrombus formation and subsequent intimal growth by using a repeated balloon-injury model in rabbits. Methods and Results-Rabbit iliac arteries 4 weeks after a fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…6,7,8 We and others have also demonstrated the contribution of vWF to the interaction between platelets and fibrin 29,30 and also fibrin-rich thrombus formation. 10 The occlusive thrombi in this study were composed of a large amount of fibrin and platelets and were rich in vWF. The presence of vWF in the occlusive thrombi suggests that vWF plays an important role in this process.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…6,7,8 We and others have also demonstrated the contribution of vWF to the interaction between platelets and fibrin 29,30 and also fibrin-rich thrombus formation. 10 The occlusive thrombi in this study were composed of a large amount of fibrin and platelets and were rich in vWF. The presence of vWF in the occlusive thrombi suggests that vWF plays an important role in this process.…”
mentioning
confidence: 79%
“…Our previous studies also demonstrated that the repeated balloon injuries of rabbit aortas and femoral arteries induce fibrin-rich mural thrombi, but do not become occlusive. 10,17 These results suggest that not only increased vascular thrombogenicity but also other factors are required to propagate arterial occlusive thrombi.Blood flow is one of the most important modulators of thrombus formation and propagation. Plaque disruption initiates thrombus formation at the disrupted site and frequently causes a reduction in coronary blood flow.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…This strategy circumvents signal correction for the transient response to steady-state magnetization, which depends on flow velocity, FA, TR, and T 1 (19). All ROIs were placed at least 9 cm distal from entry into the image slab, which satisfies the required 7 cm under our experimental settings using an assumed maximum velocity of 16 cm/second in the rabbit iliac artery (20). Time to acquire the center of k-space can be adjusted using alternative sampling schemes, such as elliptical-centric.…”
Section: Discussionmentioning
confidence: 99%